DETACHMENT FOLDING, FOLD AMPLIFICATION, AND DIAPIRISM IN THRUST WEDGE EXPERIMENTS - Bonini M. (My University, 2003)
The relations between detachment folding, fold amplification, and salt diapirism in contractional settings have been investigated by means of scaled analogue models. The viscosity of the silicone layer simulating salt in nature and the shortening rates were combined in order to reproduce weak (type 1 models) and strong (type 2 models) décollements. Deformation patterns in the roof sequence exhibited two contrasting styles, (1) outward propagation of detachment folding along the décollement (OFP mode) and (2) passive roof duplex (PRD mode). In type 2 models, detachment folding propagated away from the most external thrust in the floor sequence, while in type 1 models, long-lived detachment folds almost invariably localized amplified above a floor thrust tip as a result of strain localization. A silicone wall intruded occasionally into the crestal graben of detachment folds in type 1 and OFP models. Best fitting of transition models data points indicates nonlinear relations with regression curves close to the equilateral hyperbola equation for both OFP-PRD and amplified detachment folds-box folds transitions. A quantitative comparison of model results with nature has been attempted by plotting salt-based fold-and-thrust belts data points on the scaled transition curves obtained from the modeling. Such a comparison relates shear stress products and ratios to the conditions favoring the amplification of detachment folds and the potential emplacement of ductile diapirs in their core. By reducing the roof sequence strength, pore fluid pressure λb is inferred to shift the equilibrium of fold-and-thrust belts toward the field of OFP and diapirism.
Keywords: fold-and-thrust belts; analogue modeling; salt tectonics; detachment folding; fold amplification; passive roof duplexes